(untitled) (Publicacions de la Universitat de València, 2019)
This study examines the fiction of contemporary American author George Saunders in terms of how it presents situations applicable to the chief notions of posthumanist ethics and how these conceptions concern nonhuman animals, which are prevalent in his writing. Posthumanist ethics can help us understand what is at play in Saunders’s fiction. Meanwhile, his texts can help us understand what is at stake in posthumanist ethics. This interdisciplinary project may be beneficial both to conceiving new notions of ethics that are more inclusive and, more implicitly, to understanding the relevance of Saunders’s fiction to the current American sociocultural climate. Este estudio examina la ficción del autor estadounidense contemporáneo George Saunders: cómo presenta situaciones aplicables a las principales nociones de la ética posthumanista y cómo estas concepciones conciernen a los animales no humanos, que prevalecen en sus escritos. La ética posthumanista puede ayudarnos a entender lo que está en juego en la ficción de Saunders, mientras que sus textos pueden ayudarnos a entender lo que está en juego en la ética posthumanista. Este proyecto interdisciplinario puede ser beneficioso tanto para concebir nuevas nociones de ética que sean más inclusivas como, más implícitamente, para comprender la relevancia de la ficción de Saunders en el actual clima sociocultural estadounidense.